Andrographolide Sulfonates and Xiyanping: A Review of Chemical Composition, Pharmacological Activities, Clinical Applications, and Adverse Reactions - Zihong Li; Lihao Yao; Zhenjie Liu; Liuping Wang; Huini Ruan; Yuanle Shen; Peng Zhang; Kaitong Li; Honglan Wang; Lili Fan; Liangxing Tu; Jianfang Feng (Pharmaceuticals)
Andrographis paniculata is a plant of the Acanthaceae family and its primary bioactive constituent, andrographolide, exhibits a broad spectrum of pharmacological activities and notable clinical efficacy. However, its poor solubility and limited bioavailability pose significant challenges for therapeutic applications. To overcome these limitations, researchers have synthesized andrographolide sulfonates by reacting andrographolide with ethanol and sulfuric acid. This sulfonated derivative significantly enhances water solubility and bioavailability while retaining key pharmacological properties such as anti-inflammatory and antiviral activities. As a representative formulation, Xiyanping injection has been widely employed in the treatment of respiratory infections, pneumonia, and related conditions, playing a critical role during the COVID-19 pandemic. Despite its widespread application, there has yet to be a comprehensive review of its chemical composition and pharmacological mechanisms. Additionally, the safety of Xiyanping injection remains a topic of some debate. This review systematically examines the chemical composition, pharmacological activities, clinical applications, and adverse reactions of andrographolide sulfonates and their formulation in Xiyanping injection to provide a scientific basis for further research and applications, while also offering valuable insights for the development of similar sulfonated drugs.